2016
DOI: 10.4103/0019-5545.196704
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity suicide and its effect on further media reporting and portrayal of suicide: An exploratory study

Abstract: Background:Suicide is a grave mental health problem in India, and suicide rates in India have risen over the past decades. Suicide reporting by the media is a common cause for spurts of suicides that may occur from time to time. The aim of the present study was to assess the change in trends in media reporting of suicide after a celebrity suicide.Methodology:Suicide by the renowned actor Robin Williams was selected as the reference case. The top three Indian daily newspapers published in English having the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(26 reference statements)
1
7
0
1
Order By: Relevance
“…The overall percentage of articles speculating or jumping to conclusions (36.7%) was similar to the results of Creed and Whitley (34.8%) [ 23 ] and Utterson et al’s (30.1%) [ 26 ] studies. Similarly, the results for providing hotline information (1.4%) and educating the public (2.2%) aligned with the studies by Ramadas and Kuttichira [ 24 ] and Harshe et al [ 25 ], who found nearly zero cases for these guideline items. Contrary to other international studies that showed less than 30% of discordance in providing extensive details about the method, site/location, and suicide note, our findings showed much higher percentages of discordance with these items—68.2, 74.5 and 44.6%, respectively—in South Korea [ 16 , 25 , 26 , 37 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The overall percentage of articles speculating or jumping to conclusions (36.7%) was similar to the results of Creed and Whitley (34.8%) [ 23 ] and Utterson et al’s (30.1%) [ 26 ] studies. Similarly, the results for providing hotline information (1.4%) and educating the public (2.2%) aligned with the studies by Ramadas and Kuttichira [ 24 ] and Harshe et al [ 25 ], who found nearly zero cases for these guideline items. Contrary to other international studies that showed less than 30% of discordance in providing extensive details about the method, site/location, and suicide note, our findings showed much higher percentages of discordance with these items—68.2, 74.5 and 44.6%, respectively—in South Korea [ 16 , 25 , 26 , 37 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the study by Ramadas and Kuttichira [ 24 ], 37% of cases ( N = 3270) included photographs of the deceased, the method, and the scene. Harshe et al [ 25 ] separated the visual contents section into three specific guideline items. Out of 708 cases, 20.29% had “a photograph of the victim,” 11.98% had “a photograph of the location” and 14.42% had “a graphical illustration to depict the suicide/location,” meaning that in total, 46.69% included some type of visual contents within the article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 58 % articles used sensational language, 59.5 % articles mentioned suicide site, 17 % articles suggested possible cause for suicide which was not related to poor mental health. A study assessing the quality of suicide reporting in Indian print media found increase in prominence of suicide reports after the celebrity suicide ( Harshe et al, 2016 ). It speculated that the most likely reason for sensationalism in media reporting of suicide might be to enhance the readership.…”
Section: Discussionmentioning
confidence: 99%
“…There has been limited literature available assessing the quality of media reporting of suicide in India. Most of the studies assessed media reporting of suicide in general population, and only one study had focused on celebrity suicide specifically ( Harshe et al, 2016 ). However, that study took death of Robin Williams (Hollywood movie actor of US origin) as the reference event and was done about four years back.…”
Section: Introductionmentioning
confidence: 99%